Basic education planning in Spain 1978-2016: Concepts, laws and models - Souza, Donaldo Bello de (Education Policy Analysis Archives, 2021)
This study aims to analyze the basic education planning in Spain (1978-2016), in light of its repercussions in three basic dimensions: theoretical-conceptual, legal-normative and methodological. Respectively, it aims to signal consensus and dissent among the various perspectives about the concept of Education Planning, identify the contexts and links of educational reforms to education planning and distinguish the planning models based on the typologies of George Psacharopoulos and Hans Weiler. It results from an exhaustive documentary survey, carried out in the period 2017-2018, in loco, around articles in scientific journals, doctoral theses, books and book chapters published in this country. As a main conclusion, it postulates that the planning of education in the country have been transiting from quantitative to qualitative approaches, going from the close bindings to the economical-developmentalist planning toward the consolidation of political-social senses and values with bigger amplitude, moving from the monopoly of central administrations to regional and local spheres, from the centrality of education systems to intra-school contexts, from the technocracy cartels and expertise to the participative processes referring to diverse social actors, coherently with a global agenda for public education policies and with Spain's economic and cultural integration into the international arena.